Symbolizm jako modus cogitandi i modus vivendi. Pojęcie symbolu w myśli Andrieja Biełego . - Czardybon, Barbara (Przegląd Rusycystyczny, 2011)
СИМВОЛИЗМ КАК MODUS COGITANDI И MODUS VIVENDI. ПОНЯТИЕ СИМВОЛА В МЫШЛЕНИИ АНДРЕЯ БЕЛОГО Резюме В статье рассматриваются теорию символизма Андрея Белого (1880–1934). Белый является выдающимся теоретиком русского символизма, который смотрит сквозь призму творчества на жизнь целиком. Символизм — это для него modus co-gitandi и modus vivendi. Это особенный способ понимания мира и образ жизненной активности. SYMBOLISM AS MODUS COGITANDI AND MODUS VIVENDI. THE CONCEPT OF SYMBOL IN THE THOUGHT OF ANDREY BELY Summary The article discusses Andrey Bely’s (1880–1934) theory of symbolism. Bely is an outstanding theoretician of Russian symbolism, which looks at life in its entirety through the prism of creation. Symbolism is modus cogitandi and modus vivendi. It is a characteristic way of understanding the world and a picture of a living activity.